Merging of finance and accounting in the course of the merging of universities - XIE Jia-qi; GE Xiang-fu (浙江大学学报. 农业与生命科学版)
To counter the practice of the merging of universities, The authors studied the new resulting from the merging of finance and accounting in the course of the merging of the universities, analysed the relationship between the merging of finance and accounting and that of the universities, expounded the principles by which the merging of finance and accounting must abide, and advance the new methods and solutions.